THE MEDIATING ROLE OF SELF-EFFICACY: HOW SELF-LEADERSHIP DRIVES ACADEMIC PERFORMANCE IN EFL LEARNERS - Fetty Poerwita Sary; Alia Afiyati (Indonesian EFL Journal, 2026)
This study investigates the influence of self-leadership on academic performance, the mediating role of self-efficacy, and how these constructs interact in shaping student outcomes. Using a quantitative approach, data were collected from 72 English major students in one of the private university in East Jakarta through a structured questionnaire measuring self-leadership, self-efficacy, and academic performance. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that self-leadership directly enhances academic performance, but its strongest impact occurs indirectly through self-efficacy. The findings suggest that students’ ability to regulate their behaviors, maintain motivation, and engage in constructive self-dialogue builds confidence in their capacity to succeed, ultimately leading to better academic outcomes. This study concludes that fostering self-leadership and self-efficacy is essential for EFL learners to thrive academically. However, given the modest sample size (N = 72, the findings should be interpreted with caution as they may limit the generalizability of the results. Practical implications include integrating self-leadership training and efficacy-building interventions into English language curricula to strengthen learner autonomy, resilience, and long-term success, such as incorporating structured self-leadership modules, guided reflective exercises, and targeted efficacy-enhancement activities within classroom practice to support measurable improvements in students’ academic outcomes.